The Phenetic Distances of Jordanian Arabs from Other Human Populations Suggest a Major Genetic Drift from the Caucasoid Race - Firas Alsoleihat; Ameen Khraisat (Dental Anthropology Association, 2011)
The objectives were to determine the expression frequency and sexual dimorphism of 16 non-metric crown traits on the permanent dentitions of the living Jordanians, and to assess the biological affinity of this sample to 21 high-order groups based on these traits. 360 Jordanian school children (176 males, 184 females; mean ages 15.5, sd = 0.4 years) were studied in 2009. The traits were classified using the Arizona State University dental anthropology system, counted with the individual count method, and dichotomized according to Scott and Turner criteria for the purpose of group comparisons. Z-value test was used to assess sexual dimorphism in these traits. Smith's Mean Measure of Divergence was used to measure all pairwise distance values among the groups. Sexual dimorphism was found in only three traits (i.e., Carabelli's tubercle/cusp, metaconule and hypoconulid absence). This study revealed that the dental pattern of living Jordanians is sufficiently distinct from the Caucasoid pattern and all other known dental patterns to warrant a unique dental pattern for this population. Moreover, the relatively large distance values between the living Jordanians and all other world groups considered including the Western Eurasian groups suggest a major genetic drift for this population from the Caucasoid race.